(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2020)
The overall transportation process is a gripping activity for goats and sheep. Goats and sheep can experience stress as reflected by indicators of weight loss, physiological responses and blood metabolites. The use of sheep goat and sheep conveyance according to the Regulation of the Minister of Agriculture of the Republic of Indonesia number 114/Permentan/PD.410/9/2014concerning the transportation of sacrificial animals, vehicles can be designed for a maximum of two decks. Farmers use pick-up vehicles arranged in three levels to reduce transportation costs. This study uses two triple-deck pick-up vehicles for 60 goats and 60 sheep. Each deck is filled with 20 animals and five animals are taken as samples. The design used by using a randomized block design (RBD), the position of the deck (deck 1, deck 2, deck 3) as a factor, and body weight as groups. The evaluation results of goat and sheep transportation with a distance of ± 674 km (± 16 hours of travel) shows that deck has no significant effect (P>0.05) on the weight loss of goat and sheep also did not affect (P>0.05) on the physiological response and blood metabolites. The stress level of goats and sheep transported is not affected by deck position.